Mapping knowledge structure and research of the biologic treatment of asthma: A bibliometric study - Sun, Jiamin; Bai, Shiyao; Zhao, Jieyu; Li, Danling; Ma, Xueqing; Ma, Lin; Su, Xinming (Frontiers in Immunology, 2023)
Background Bronchial asthma (asthma) is a chronic inflammatory disease of the airways, involving a variety of cells and cellular components, that manifests clinically as recurrent episodes of wheezing, shortness of breath, with or without chest tightness or cough, airway hyperresponsiveness, and variable airflow limitation. The number of people with asthma has reached 358 million worldwide and asthma causes huge economic loss. However, there is a subset of patients who are not sensitive to existing drugs and the existing drugs have many adverse effects. Therefore, it’s important to find new drugs for asthma patients. Methods Publications related to biologics in asthma published from 2000 to 2022 were retrieved from Web of Science Core Collection. The search strategies were as follows: topic: TS=(biologic* OR “biologic* product*” OR “biologic* therap*” OR biotherapy* OR “biologic* agent*” OR Benralizumab OR “MEDI-563” OR Fasenra OR “BIW-8405” OR Dupilumab OR SAR231893 OR “SAR-231893” OR Dupixent OR REGN668 OR “REGN-668” OR Mepolizumab OR Bosatria OR “SB-240563” OR SB240563 OR Nucala OR Omalizumab OR Xolair OR Reslizumab OR “SCH-55700” OR SCH55700 OR “CEP-38072” OR CEP38072 OR Cinqair OR “DCP-835” OR DCP835 OR Tezspire OR “tezepelumab-ekko” OR “AMG-157” OR tezspire OR “MEDI-9929” OR “MEDI-19929” OR MEDI9929 OR Itepekimab OR “REGN-3500”OR REGN3500 OR “SAR-440340”OR SAR440340 OR Tralokinumab OR “CAT-354” OR Anrukinzumab OR “IMA-638” OR Lebrikizumab OR “RO-5490255”OR “RG-3637”OR “TNX-650”OR “MILR1444A”OR “MILR-1444A”OR”PRO301444”OR “PRO-301444”OR Pitrakinra OR altrakincept OR “AMG-317”OR”AMG317” OR Etokimab OR Pascolizumab OR “IMA-026”OR Enokizumab OR “MEDI-528”OR “7F3COM-2H2” OR 7F3COM2H2 OR Brodalumab OR “KHK-4827” OR “KHK4827”OR “AMG-827”OR Siliq OR Ligelizumab OR “QGE-031” OR QGE031 OR Quilizumab OR Talizumab OR “TNX-901” OR TNX901 OR Infliximab OR Etanercept OR “PRS-060”) AND TS=asthma*. The document type was set to articles and review articles and the language restriction was set to English. Three different analysis tools including one online platform, VOS viewer1.6.18, and CiteSpace V 6.1.R1 software were used to conduct this bibliometric study. Results This bibliometric study included 1,267 English papers published in 244 journals from 2,012 institutions in 69 countries/regions. Omalizumab, benralizumab, mepolizumab, and tezepelumab in relation to asthma were the research hotspots in the field. Conclusion This study systematically uncovers a holistic picture of existing literature related to the biologic treatment of asthma over the past 20 years. We consulted scholars in order to understand key information in this field from the perspective of bibliometrics, which we believe may greatly facilitate future research in this field.